2014
DOI: 10.1016/j.immuni.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Mode of ERK Action Controls Alternative αβ and γδ T Cell Lineage Fates

Abstract: SUMMARY Gradations in ERK signaling have been implicated in essentially every developmental checkpoint or differentiation process encountered by lymphocytes. Yet, despite intensive effort, the molecular basis by which differences in ERK activation specify alternative cell fates remains poorly understood. We report here that differential ERK signaling controls lymphoid fate specification through an alternative mode of action. While ERK phosphorylates most substrates, such as Rsk, by targeting them through its D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…TCR signalling involves activation of the PKCθ pathway, leading to activation of NFκB; the PI3K pathway, leading to activation of NFAT; and the MAPK signalling pathway (in particular, ERK), which is upstream of many inducible transcription factors, including Egr3 34 . MAPK signalling and Egr3 activity have been linked to the αβ/γδ T cell 19 and γδT17/γδT1 cell lineage choices 17 , 35 , 36 , in agreement with the signal strength model. However, other experiments have indicated that strong TCR signals are needed for the development of at least some γδT17 cells 16 .…”
Section: Introductionsupporting
confidence: 71%
“…TCR signalling involves activation of the PKCθ pathway, leading to activation of NFκB; the PI3K pathway, leading to activation of NFAT; and the MAPK signalling pathway (in particular, ERK), which is upstream of many inducible transcription factors, including Egr3 34 . MAPK signalling and Egr3 activity have been linked to the αβ/γδ T cell 19 and γδT17/γδT1 cell lineage choices 17 , 35 , 36 , in agreement with the signal strength model. However, other experiments have indicated that strong TCR signals are needed for the development of at least some γδT17 cells 16 .…”
Section: Introductionsupporting
confidence: 71%
“…By contrast, a body of evidence instead suggests that γδ 17 cell development requires weak (or even absent) TCR γδ signalling . For example, generation of γδ 17 cells is favoured by the reduction of ERK activity . In addition, V γ 5V δ 1 + γδ T cells developing in the absence of Skint1 adopt IL‐17‐secreting characteristics .…”
Section: Il‐17‐secreting γδ T‐cell Developmentmentioning
confidence: 99%
“…Activation of the extracellular signal‐regulated kinase (ERK) pathway appears to be important, which can induce early growth response (Egr) family transcription factors and inhibitor of DNA binding 3 (Id3) . More recently, non‐canonical targeting of docking site for ERK, FXF (DEF) domain containing ERK substrates through the ERK DEF‐binding pocket has also been implicated in γδ T‐cell fate commitment . Hence, strong TCR signalling delivered mainly by TCR‐ γδ complexes drives DN cell commitment to the γδ T‐cell lineage.…”
Section: Thymocyte Commitment To a γδ T‐cell Fatementioning
confidence: 99%
“…More recent work has begun to shed light on the mechanism by which DN cells translate differences in signal strength and ERK signaling into alternative lineage fates. γδ T cell development is dependent on a non-canonical mode of ERK action mediated by its DEFbinding pocket (29). This domain is favored by strong and more prolonged signals and enables ERK to bind a distinct set of proteins required for γδ lineage adoption.…”
Section: γδ Lineage Commitment In the Thymusmentioning
confidence: 99%
“…γδ T cell effector fate choice is also influenced by specific TCR signal transduction pathways. For example, ERK signals support the type 1 program as ERK-deficient TCRβ −/− mice have an increased frequency of CD27 − γδ T cells, and ERK-deficient KN6 γδ TCR transgenic thymocytes are skewed toward IL-17A production compared to the controls that predominately produce IFNγ (29). More recently, it was revealed that the tyrosine kinase Syk is selectively required for Tγδ17 development, through activation of the PI3K/Akt pathway downstream of γδTCR signaling (58).…”
Section: Role Of γδTcrmentioning
confidence: 99%